Experimental studies on ion mobility in xenon-trimethylamine mixtures. (5th July 2017) - Trindade, A.M.F.; Encarnação, P.M.C.C.; Escada, J.; Cortez, A.F.V.; Neves, P.N.B.; Conde, C.A.N.; Borges, F.I.G.M.; Santos, F.P.
Abstract: In this paper we present experimental results for ion reduced mobilities ( K 0 ) in gaseous trimethylamine, TMA—(CH 3 ) 3 N, and xenon-TMA mixtures for reduced electric fields E / N between 7.5 and 60 Td and in the pressure range from 0.5 to 10 Torr, at room temperature. Both in the mixtures and in pure TMA only one peak was observed in the time of arrival spectra, which is believed to be due to two TMA ions with similar mass, (CH 3 ) 3 N + (59 u) and (CH 3 ) 2 CH 2 N + (58 u), whose mobility is indistinguishable in our experimental system. The possibility of ion cluster formation is also discussed. In pure TMA, for the E / N range investigated, an average value of 0.56 cm 2 V −1 s −1 was obtained for the reduced mobility of TMA ions. For the studied mixtures, it was observed that even a very small amount of gaseous TMA ( ∼ 0.2%) in xenon leads to the production of the above referred TMA ions or clusters. The reduced mobility value of this ion or ions in Xe-TMA mixtures is higher than the value in pure TMA: around 0.8 cm 2 V −1 s −1 for TMA concentrations from 0.2% to about 10%, decreasing for higher TMA percentages, eventually converging to the reduced mobility value in pure TMA.